Implementasi Chatbot Whatsapp Untuk Sistem Informasi Laundry Di Laundryku - Arif Siswandi; Haryo Seto Muhamad (Prosiding Sains dan Teknologi, 2025)
This research aims to implement a WhatsApp chatbot within the Laundryku information system to enhance service quality and operational efficiency. The system is developed using the Waterfall method, which includes structured stages such as requirement analysis, system design, implementation, testing, and maintenance. This method ensures that the development process is systematic, organized, and well-documented. The chatbot is built using the TypeScript programming language along with several libraries from Baileys to enable integration with the WhatsApp platform. TypeScript is chosen for its strong support in web application and API development, as well as its ability to reduce errors through structured typing. By leveraging WhatsApp, a platform widely used and familiar to customers, the system ensures accessibility and ease of communication. The implemented chatbot is designed to facilitate customer interactions, including service booking, order status tracking, and access to additional information about laundry services. Through automation, the system minimizes manual communication, improves response time, and enhances service efficiency. Overall, the implementation of this WhatsApp chatbot is expected to improve customer experience while supporting Laundryku in optimizing its digital-based business operations.